Corak Nalar Falsafah Kalam Abu al-Asy’ari dalam al-Luma’ - Syahuri Arsyi (UIN Sunan Kalijaga Yogyakarta, 2022)
The subject of this article is the philosophical reasoning patterns in the work of Abu Hasan al-Asy'ari, titled